2008
DOI: 10.1021/jm701319c
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of C-17 Cyano-Substituted Estratrienes as Anticancer Agents

Abstract: The synthesis, SAR, and preclinical evaluation of 17-cyanated 2-substituted estra-1,3,5(10)-trienes as anticancer agents are discussed. 2-Methoxy-17beta-cyanomethylestra-1,3,5(10)-trien-3-ol ( 14), but not the related 2-ethyl derivative 7, and the related 3- O-sulfamates 8 and 15 display potent antiproliferative effects (MCF-7 GI 50 300, 60 and 70 nM, respectively) against human cancer cells in vitro. Investigation of the SAR reveals that a sterically unhindered hydrogen bond acceptor attached to C-17 is most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 45 publications
6
57
0
Order By: Relevance
“…Crystal structure of hCA II in complex with compound 3 was determined at 1.80 Å resolution, revealing a clear electron density for the inhibitor molecule in the enzyme active site (Figure 2 [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] , compound 1 interacts directly with the zinc ion of the active site, with its sulphamate nitrogen atom N1 (for atom numbering see Figure 1) displacing the water molecule/hydroxide ion, which in the not-inhibited enzyme occupies the fourth coordination position. Additional hydrogen bonds between the sulphamate moiety and residues within the enzyme active site contribute to stabilise the binding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structure of hCA II in complex with compound 3 was determined at 1.80 Å resolution, revealing a clear electron density for the inhibitor molecule in the enzyme active site (Figure 2 [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] , compound 1 interacts directly with the zinc ion of the active site, with its sulphamate nitrogen atom N1 (for atom numbering see Figure 1) displacing the water molecule/hydroxide ion, which in the not-inhibited enzyme occupies the fourth coordination position. Additional hydrogen bonds between the sulphamate moiety and residues within the enzyme active site contribute to stabilise the binding.…”
Section: Resultsmentioning
confidence: 99%
“…To understand if the different position assumed by N2 and O3 atoms in the enzyme active site was associated to a peculiarity of the two complexes under investigation, or to a more general behaviour of sulphamate and sulphamide derivatives, a comparative analysis of all hCA II/sulphamate and hCA II/sulphamide structures available in the PDB was undertaken 25,26,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][67][68][69][70][71] . Surprisingly, the analysis of all these structures revealed that, independently of the nature of the moiety attached to the ZBG, the distance between the Thr200OG1 atom and the sulphamide nitrogen N2 in hCA II/sulphamide complexes was generally shorter than the corresponding distance between the sulphamate oxygen O3 and the same enzyme atom in hCA II/sulphamate complexes (see Tables 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
“…These include steroid sulfatase inhibitors EMATE (39) and STX64 (40), two examples of a dual aromatase sulfatase inhibitor (41), 2-MeOE2bisMATE, a multitargeted antitumor agent (37), and a related agent STX641 (42). Given the excellent potency of (4) against hCAII, we explored cocrystallization of (4) with the enzyme and now report the interaction of this compound with hCAII using protein crystallography (Fig.…”
mentioning
confidence: 99%
“…The indene core compound 3d was also synthesized from a Hajos-Parrish ketone (6), 35,36) following the same procedure as described for compound 3c (Chart 5).…”
Section: Fig 2 Synthetic Strategy For Rgd Mimics 3a-ementioning
confidence: 99%